(untitled) (Pedagogical Horizons, 2018)
The public discourse on Muslims leads to a prejudiced perception of Islam and the associated theological content. As a result, Islam is often equated with a threat. This results in a debate of Islam’s ability of a peaceful coexistence with other religions. To deal with this discussion, an analysis of the Islamic sources is necessary.